2021
DOI: 10.1136/bmjdrc-2021-002426
|View full text |Cite
|
Sign up to set email alerts
|

Association between type 2 diabetes and chronic low back pain in general practices in Germany

Abstract: IntroductionThere are conflicting results on the association between type 2 diabetes and chronic low back pain (CLBP). Therefore, the goal was to investigate the relationship between type 2 diabetes and CLBP in individuals followed in general practices in Germany.Research design and methodsAdults diagnosed for the first time with type 2 diabetes in 809 general practices in Germany between 2005 and 2018 (index date) were included. Adults without type 2 diabetes were matched (1:1) to those with type 2 diabetes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The figures were around twice as high for spinal pain and almost three-fold for MFH. This significantly higher presence of self-reported pain among women was frequently found in previous studies conducted in Spain and other countries [ 8 , 10 , 11 , 12 , 16 , 24 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The figures were around twice as high for spinal pain and almost three-fold for MFH. This significantly higher presence of self-reported pain among women was frequently found in previous studies conducted in Spain and other countries [ 8 , 10 , 11 , 12 , 16 , 24 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 80%
“…Different authors have suggested possible reasons to explain these sex differences in people with diabetes [ 8 , 12 , 24 ]. Glycemic control is poorer in women than in men with diabetes; therefore, low-grade systemic inflammation may be more severe in women than in their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations